2018
DOI: 10.1080/07420528.2018.1515771
|View full text |Cite
|
Sign up to set email alerts
|

Night work effects on salivary cytokines TNF, IL-1β and IL-6

Abstract: Shift work is unavoidable in modern societies, but at the same time disrupts biological rhythms and contributes to social distress and disturbance of sleep, health and well-being of shift workers. Shift work has been associated with some chronic diseases in which a chronic inflammatory condition may play a role. However, few studies investigating the association of cytokine and other inflammation markers with shift workers have been published in recent years. In this study we evaluated the effects of permanent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 66 publications
1
28
0
Order By: Relevance
“…Briefly, the normal rhythmic secretion of melatonin can guarantee sufficient levels of serum concentration required for an anti-inflammatory effect. It was also found that night work can disturb the secretion of melatonin in healthy male workers, resulting in the lift of TNF, IL-1 and IL-6 in their saliva [30]. In the present study, melatonin could promote COL2 and aggrecan synthesis and inhibit MMP-3 production.…”
Section: Discussionsupporting
confidence: 56%
“…Briefly, the normal rhythmic secretion of melatonin can guarantee sufficient levels of serum concentration required for an anti-inflammatory effect. It was also found that night work can disturb the secretion of melatonin in healthy male workers, resulting in the lift of TNF, IL-1 and IL-6 in their saliva [30]. In the present study, melatonin could promote COL2 and aggrecan synthesis and inhibit MMP-3 production.…”
Section: Discussionsupporting
confidence: 56%
“…Melatonin levels in saliva collected at midday in normal children were between 6 and 11 pg/mL with this assay while the threshold for calculating DLMO in adults was 10.4 pg/mL . Some recent studies have however reported levels of 0.8‐2 pg/mL in adults at 14:00 hours . The reasons for this inter‐laboratory variation are not known.…”
Section: Melatonin Measurementmentioning
confidence: 81%
“…74 Some recent studies have however reported levels of 0.8-2 pg/mL in adults at 14:00 hours. 75,76 The reasons for this inter-laboratory variation are not known.…”
Section: Saliva Elisamentioning
confidence: 99%
“…The consequence of this misalignment is a heightened pro-inflammatory response exclusively due to the phase-shift in the light-dark cycle, rather than concurrent sleep loss [158]. Regimens of ECD also impact metabolic processes on whole-body, macroscopic [159] and microscopic scales (heart [160]; skeletal muscle [161]; liver [162]) similar to what has been reported in human models of sleep loss compounded by shift work [54, 163, 164]. Animal models of constant light and constant darkness can desynchronize the suprachiasmatic nucleus (SCN) and alter gene activity [68, 69], and can further our understanding of the consequences of extended shift work and night operations in military personnel.…”
Section: Introductionmentioning
confidence: 89%